The Night - Sáenz, Jaime (Book collections on Project MUSE., 2007)
"In this poem, Jaime Saenz explores the singular themes that possessed him: alcoholism, death, nightmares, identity, otherness, and his love for La Paz. The poem's four movements culminate in some of the most profoundly mystical, beautiful, and disturbing passages of modern Latin American poetry. They are presented here in this faithful and inspired English translation of the Spanish original." "Complete with an introduction by the translators that paints a picture of the poet's life, and an afterword by Luis H. Antezana, a Bolivian literary critic and close friend of Saenz, this bilingual edition is the essential introduction to one of the most visionary and enigmatic poets of the Hispanic world."--Jacket